Free Cash Flow, Profitabilitas, Kebijakan Hutang, dan Likuiditas terhadap Kebijakan Dividen - Syamsuddin, Fajar Rakasiwi (Universitas Gorontalo, 2023)
This study aims to determine the effect of free cash flow, profitability, leverage and liquidity on dividend policy (an empirical study of pharmaceutical companies listed on the Indonesian stock exchange. Multiple regression analysis is used to determine the significance of the independent variables on the dependent variable. Types of data in this research is quantitative data in the form of numbers from the company's financial statements which are the object of research to be further converted into ratio values. The sampling technique used in this research is purposive sampling method. The research samples are pharmaceutical companies listed on the Indonesian stock exchange with consistent criteria for publishing annual reports from 2018 to 2022. This study found that profitability has a positive and significant effect on dividend policy. That is, if the company generates profits, the company will distribute it as dividends. Free cash flow, debt and liquidity policies have no significant effect on the company's dividend policy.